EPIDEMIOLOGICAL AND PATHOLOGICAL ASPECTS OF HORN CANCER IN CATTLE OF GUJARAT - Joshi, B P; Soni, P B; Fefar, D T; Ghodasara , D J; Prajapati , K S (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The present study was carried out to know prevalence, and the gross and histopathological lesions of bovine horn cancer in Bos indicus in Gujarat. The material was collected from college hospital, Clinics and Dept. of Surgery at Anand as well as by personal visits to other areas of Gujarat. Prevalence of occurrence of horn cancer was observed more in males (15/18) than females (3/18). The risk of this condition was found between the age group of 5 to 6 years (11.11%), 7-10 years (72.22%) and 10 to 12 years (16.66%). Prevalence of horn cancer was observed more in Kankrej breed (16/18) than Gir breed (2/18) of cattle. The most consistent clinical signs observed were frequent shaking of head, tilting of head at the affected side, bending of affected horn and increase nasal discharge from the nose of affected side in advance cases. Microscopic examination of cancerous tissue collected from middle region of horn core in all the three stages of horn cancer revealed typical keratinizing squamous cell carcinoma with characteristic epithelial pearls. The cell mass consisted of concentric layer of squamous cells showing gradually increasing keratinization towards the center.